Attending to local form while ignoring global aspects depends on handedness: evidence from TMS. - Mevorach, C; Humphreys, G; Shalev, L (2005)
Our perceptions of the whole and of the parts of a visual stimulus are mediated by different brain regions. We used low-frequency transcranial magnetic stimulation (TMS) to show for the first time that opposite, homologous regions in the two hemispheres are involved in attending to local parts for left- and right-handed individuals. The brain regions that focus on the 'trees' while ignoring the 'forest' are switched as a function of handedness.